The History of Law by trade - Ortego, Pedro (Cuadernos de Historia del Derecho, 2024)
For five decades, Professor José Sánchez-Arcilla Bernal turned his research and teaching activity into a profession with exclusive dedication to the History of Law and Institutions, a career that is reviewed in this work.
Keywords: History of Law; investigation; teaching